Peran Sub Bagian Tata Usaha dan Kepegawaian dalam Peningkatan Kualitas Kinerja di Sekretariat DPRD Kota Tanjungpinang Tahun 2025 - Shiwy Wulandari; Kustiawan Kustiawan; Adhe Fadli Farhan (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This research looks at the role of the Administration and Staffing Subdivision in Improving the Quality of Performance of the DPRD Secretariat of Tanjungpinang City. This proves the importance of the sub-section that has duties in the field of administration and staffing. By using descriptive research through a qualitative approach, this research analyzes the roles of the staff or employees of the Administration and Staffing Subdivision. The purpose of this research is to find and analyze the roles of employees based on indicators of active roles, participation roles, and passive roles. The results showed that the role of the Administration and Personnel Subdivision was very optimal in improving the quality of performance of the Tanjungpinang City DPRD Secretariat. This can be seen from the Subdivision's ability to manage administration and staffing effectively, thus supporting the achievement of organizational goals. In addition, good coordination between sections and the implementation of a structured work system are also important factors in improving work efficiency and productivity.